Analysis of Adverse Events in the Management of Chronic Migraine by Peripheral Nerve Stimulation. Issue 4 (14th October 2014) - Sharan, Ashwini; Huh, Billy; Narouze, Samer; Trentman, Terrence; Mogilner, Alon; Vaisman, Julien; Ordia, Joe; Deer, Timothy; Venkatesan, Lalit; Slavin, Konstantin
<x xml:space="preserve">Abstract</x> Objective In this study, we analyze device‐ and procedure‐related adverse events (AEs) from a recent prospective, multicenter, double‐blinded controlled study that utilized peripheral nerve stimulation (PNS) of occipital nerves for management of chronic migraine. Methods PNS device characteristics (lead length and spacing), surgical techniques including lead orientation (parallel or perpendicular to the nerve), and implantable pulse generator (IPG) placement (upper buttock, abdomen, infraclavicular, or lower axilla) in 157 patients were analyzed to identify any relationship with the AE incidence rate. Number of prior PNS implants performed (NPPIP) by the implanter and its relationship with different AE categories (hardware‐related, biological, and stimulation‐related events) and frequently observed device/procedure‐related AEs (lead migration/fracture/breakage, persistent pain at the lead/IPG location, unintended/undesirable changes in stimulation, infection) were also evaluated. Three‐way ANOVA tests were utilized to evaluate the dependence of AE occurrence on the variables described above. Results IPG pocket locations closer to the lead (e.g. infraclavicular region) were associated with a lower AE incidence rate (p < 0.05). Higher NPPIP was related to lower stimulation‐ and hardware‐related AEs (p < 0.05), frequently observed AEs like lead migration, pain, and infection (p < 0.05), and procedure‐related additional surgeries (p < 0.05). Conclusion Implantation of the IPG closer to the lead location was associated with reduced AEs. PNS is a relatively new procedure, and the skill and precision in performing these procedures improves with experience. Our results demonstrate that as the implanter gains more experience with these procedures, a significant reduction in device‐ and procedure‐related AEs may be expected.